A histological and ultrastructural study of femoral head cartilage in a new type II collagenopathy - Su, Peiqiang (Springer-Verlag, 2010)
A new type II collagenopathy, caused by the p.Gly1170Ser mutation of COL2A1, which presents as premature hip osteoarthritis (OA), avascular necrosis of the femoral head (ANFH) or Legg-Calvé-Perthes (LCP) disease, was recently found in several families with an inherited disease of the hip joint. In this study, femoral head cartilage was harvested for histological and ultrastructural examination to determine the pre-existing generalised abnormalities of the mutant cartilage. The histological results showed that the hierarchical structure of the mutant cartilage and the embedded chondrocytes were markedly abnormal. The expression and distribution of type II collagen was non-uniform in sections of the mutant cartilage. Ultrastructural examination showed obvious abnormal chondrocytes and disarrangement of collagen fibres in the mutant cartilage. Furthermore, the predicted stability of type II collagen dramatically decreased with the substitution of serine for glycine. Our study demonstrated that the p.Gly1170Ser mutation of COL2A1 caused significant structural alterations in articular cartilage, which are responsible for the new type II collagenopathy.